First molecular approach to the benthic- shallow water octopus' fauna from the southern Caribbean, Colombian area (2018)
The cephalopod fauna of the southern Caribbean is poorly studied, specially species of the order Octopoda. The present study is the first molecular approach to assess Colombian octopus species, aiming to contribute to the knowledge of the systematics of this group locally and world-wide. Maximum Likelihood phylogenies of the family Octopodidae were constructed using cytochrome oxidase I and Rhodopsin sequences generated from specimens collected in three locations at the Colombian Caribbean Sea and other downloaded from Genbank. Additionally, species were delimited with the bGMYC method. Despite inconsistencies between the two molecular markers, our phylogenetic analyses confirmed the monophyly of three described species found in the area (Octopus hummelincki, O. briareus and O. taganga). Moreover, our results show molecular-based evidence for the distinction of the new Callistoctopus species proposed by Guerrero-Kommritz et al., (2016). Conversely, morphologically distinguished O. aff. tayrona species (Octopus spB and Octopus spD) showed no distinction at the molecular level...